Isolasi dan Identifikasi Senyawa Hasil Fermentasi Kapang Endofit Pasak Bumi (Eurycoma longifolia Jack) - Ratna Djamil; Titi Parwati; Nani Khomeni (Fakultas Farmasi Universitas Pancasila, 2004)
Endophytic fungi of Pasak bumi (Eurycoma longifolia Jack). were inoculated to synthetic medium and incubated for 28 days. The fumated medium then were extracted with chloroform. The antioxidant activities by 1,1-diphenyl 2-picrylhidrazyl (DPPH) methods showed that isolated compound has scavenging effect at IC285.7 ppm. Identification by interpretation of infra red spectra showed that the isolated compound was a terpenoid.